Biomedical Information Intelligent Access Systems: a review - Prados Frutos, Juan Carlos; Plaza Morales, Laura; Carrillo de Albornoz Cuadrado, Jorge (Revista Internacional de Ciencias Podológicas, 2010)
Modern medical environment is characterized by the work overload and the lack of time. In such an environment, intelligent information access systems can undoubtedly assist the work of physicians and researchers. Nonetheless, despite their benefits, clinical information systems barely include these technologies. Several are the reasons. First, the potential of these strategies will only be achieved once health care professionals become familiar with them. Second, it is necessary to progress in the development of patient information standards, as well as in the use of an unified and controlled terminology. Even if important advances have been reached during the last decade, there is still much work to do.
Keywords: Intelligent information access; Natural Language Processing; Unified Medical Language System (UMLS); SNOMED; Medical Subject Headings (MeSH)